Trading Fees and Efficiency in Limit Order Markets - Colliard, Jean-Edouard; Foucault, Thierry (Review of Financial Studies, 2012)
Competition among trading platforms has considerably reduced trading fees in stock markets. We show that this evolution is not necessarily beneficial to investors. Although they increase gains from trade when a trade happens, lower trading costs can induce investors to post limit orders with a smaller execution probability. In this case, gains from trade are realized less frequently and investors can be worse off. Our model has testable implications for the effects of trading fees and their breakdown between liquidity suppliers and liquidity demanders on limit order fill rates and bid-ask spreads.